Gene expression imputation identifies candidate genes and susceptibility loci associated with cutaneous squamous cell carcinoma. Issue 1 (December 2018) - Ioannidis, Nilah; Wang, Wei; Furlotte, Nicholas; Hinds, David; Bustamante, Carlos; Jorgenson, Eric; Asgari, Maryam; Whittemore, Alice
Abstract Cutaneous squamous cell carcinoma (cSCC) is a common skin cancer with genetic susceptibility loci identified in recent genome-wide association studies (GWAS). Transcriptome-wide association studies (TWAS) using imputed gene expression levels can identify additional gene-level associations. Here we impute gene expression levels in 6891 cSCC cases and 54, 566 controls in the Kaiser Permanente Genetic Epidemiology Research in Adult Health and Aging (GERA) cohort and 25, 558 self-reported cSCC cases and 673, 788 controls from 23andMe. In a discovery-validation study, we identify 19 loci containing 33 genes whose imputed expression levels are associated with cSCC at false discovery rate < 10% in the GERA cohort and validate 15 of these candidate genes at Bonferroni significance in the 23andMe dataset, including eight genes in five novel susceptibility loci and seven genes in four previously associated loci. These results suggest genetic mechanisms contributing to cSCC risk and illustrate advantages and disadvantages of TWAS as a supplement to traditional GWAS analyses. Genetic loci linked to susceptibility for the common skin cancer cutaneous squamous cell carcinoma (cSCC) have been identified by genome wide association studies (GWAS). Here, the authors impute gene expression levels from GWAS data to perform a transcriptome wide association study (TWAS), identifying five novel genetic loci linked to cSCC susceptibility.